2017
DOI: 10.1021/acs.jctc.7b00688
|View full text |Cite
|
Sign up to set email alerts
|

How To Arrive at Accurate Benchmark Values for Transition Metal Compounds: Computation or Experiment?

Abstract: With the objective of analyzing which kind of reference data is appropriate for benchmarking quantum chemical approaches for transition metal compounds, we present the following, (a) a collection of 60 transition metal diatomic molecules for which experimentally derived dissociation energies, equilibrium distances, and harmonic vibrational frequencies are known and (b) a composite computational approach based on coupled-cluster theory with basis set extrapolation, inclusion of core-valence correlation, and cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
168
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(182 citation statements)
references
References 266 publications
11
168
0
3
Order By: Relevance
“…We compare the MR-CCSD(T) and CCSD(T) values reported in Ref. 7 to the reference values, and find that the CC methods display a number of large outliers (fewer for the MR-corrected version). We also analyze the performance of 10 DFT functionals, reported in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…We compare the MR-CCSD(T) and CCSD(T) values reported in Ref. 7 to the reference values, and find that the CC methods display a number of large outliers (fewer for the MR-corrected version). We also analyze the performance of 10 DFT functionals, reported in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35] However, the reliability of CC methods for transition metal systems, even when multireference effects are approximated, has been the subject of vigorous debate, as illustrated by recent studies on transition metal diatomic-ligand systems. 24,[36][37][38][39][40][41] de Oliveira-Filho and co-workers found that even multireference CCSD(T) could not predict the bond dissociation energies (BDEs) for some diatomics accurately with respect to experimental measurements. A recent study by Head-Gordon and co-workers found that high levels of CC, up to CCSDTQ, are required for chemical accuracy against an exact method known as Adaptive Sampling Configuration Interaction (ASCI) results, albeit in a small basis set.…”
Section: Introductionmentioning
confidence: 99%
“…For small systems, accurate quantum‐chemical methods can compute the energies of bond formation and bond breaking, which enables a test of the accuracy of DFT methods used for specific systems. In particular, the use of the BDEs of metal‐ligand bonds are receiving significant attention as best‐practice benchmark properties for chemical reactivity across the d‐block . The success largely relates to the fact that the diatomic M−O BDEs correlate better than any other known single descriptor to the chemisorption energies of pure metal surfaces, with R 2 approaching 0.89 when computed with the same methods, across a range of more than 500 kJ/mol in both O 2 chemisorption energies and M−O BDEs within the d‐block.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the use of the BDEs of metalligand bonds are receiving significant attention as best-practice benchmark properties for chemical reactivity across the dblock. [30,[33][34][35][36][37][38][39][40] The success largely relates to the fact that the diatomic MÀ O BDEs correlate better than any other known single descriptor to the chemisorption energies of pure metal surfaces, with R 2 approaching 0.89 when computed with the same methods, [30] across a range of more than 500 kJ/mol in both O 2 chemisorption energies and MÀ O BDEs within the dblock. Coordinative saturation, metalÀ metal modulations and solvent effects contribute smaller errors to the DFT-modelled process than the local MÀ O bond, because the relative MÀ O bond energies vary by an order of magnitude more than the metalÀ metal modulating influences, or correspondingly, the trend in cohesive energy changes upon ligand dissociation from different metal surfaces.…”
Section: Introductionmentioning
confidence: 99%